FORESTRY DEVELOPMENT IN NGHE AN PROVINCE: THE CURRENT STATUS AND POLICY RECOMMENDATIONS - Thi Thu Ha, Tran; Minh Thanh, Nguyen; Thi Thu, Chu; Thi Xuan Huong, Nguyen (Journal of Forestry Science and Technology, 2023)
Nghe An has the biggest area of forest and forestland in the North Central region and play an important role in environmental protection, biodiversity conservation, poverty reduction and social stability. Nghe An forestry sector has achieved many results in forest protection and development, forest cover is increasing, biodiversity is preserved, the economic structure of the industry has changed positively. However, the management and protection of forest resources and the organization of forestry production currently have many limitations and shortcomings, and have not brought into full play the potential and advantages of the sector. The study was conducted to assess the status of forestry development in the period 2016-2020 and to propose policy recommendations to develop the province’s forestry sector in the 2021-2030. The main research method is to collect and analyze secondary data sources from related units. In addition, primary data and information were collected from individual interviews and group discussions with officials and local people in the province. The results have assessed the status of forestry development in the period 2016-2020 in terms of forest protection and natural conservation, concentrated new forest plantation, timber and NTFPs harvesting, forest interprises, wood processing, payment for forest environmental services, and a number of recommendations has been made to promote forestry development in Nghe An province.